Improving The Performance of The Production Process Using Six Sigma Methodology. A Case Study at The Libyan Iron and Steel Company - Dermish أميرة; Shaneb عمر; Elamin فتحي; Abugeddida رمضان (Journal of Pure & Applied Sciences, 2024)
Adhering to the specifications of industrial products is no longer sufficient at the present time with the great competition in the markets, and it has become necessary to achieve customer requirements using more advanced quality improvement methods. This research aims to study the possibility of applying Six Sigma methodology in the Libyan Iron and Steel Company, the benefits resulting from its implementation, and the obstacles that accompany the implementation process. The case was studied at the bar rolling mill plant to know the production process, production quantity, detection of defective parts, finding out the causes of defective occurrence. This was done by forming a team to determine the most important mechanical properties that will be measured (yield stress, tensile strength, elongation), and determining the number and size of samples. Sample data were collected from the rolling mill’s laboratory and analyzed by the statistical Minitab software, plotting X-bar and R (range) chart, analyzing the capability of the production process, and calculating the level of Six Sigma using DPMO. It was concluded in this study that most of the defective specimens were caused by low yield stress due to low carbon percentage. As well as, it is necessary to improve the water cooling process and periodic inspection on it. In addition, the study found that it is important to conduct training programs in order to qualify employees and train them on Six Sigma techniques and tools, as well as providing all requirements for the successful implementation of Six Sigma methodology.